Empirical study of the meaning of work measurement scale - Navajas, Rosemeire Colalillo; Cohen, Eric David (Revista Gestão da Produção Operações e Sistemas, 2020)
The meaning of work is increasingly aimed at providing fulfillment, personal identity and pursuit of professional purpose through a convergence of individual values and the work environment. This chain of events leads to a direct effect in personal motivation and organizational productivity. Accordingly, this paper aims to analyze the conceptual framework of the meaning of work model using confirmatory factor analysis, starting from a locally developed measurement scale. An empirical test is applied to data collected through a survey with 200 participants employed by a company located in the State of São Paulo, Brazil. The statistical analysis reveals the existence of two main dimensions, the first referring to justice at work, and the second to wear and dehumanization. The research demonstrates the need to employ confirmatory methods in order to provide the necessary basis for measurement scale validation with respect to the extant theory. The evidence herein presented allows us to conclude that the IMST construct is still being developed; continuous efforts are needed in order to ensure that the scale is effective and valid – in particular, with regards to the interaction between the personal and the social dimensions related to the meaning of work.